Anti-proliferative and apoptosis induction activities of extracts from Thai medicinal plant recipes selected from MANOSROI II database - Manosroi J. (2014)
Ethonopharmacological relevances: Traditional medicines have long been used by the Thai people. Several medicinal recipes prepared from a mixture of plants are often used by traditional medicinal practitioners for the treatment of many diseases including cancer. The recipes collected from the Thai medicinal text books were recorded in MANOSROI II database. Anticancer recipes were searched and selected by a computer program using the recipe indication keywords including Ma-reng and San which means cancer in Thai, from the database for anticancer activity investigation. Aim of study: To investigate anti-cancer activities of the Thai medicinal plant recipes selected from the "MANOSROI II" database. Materials and methods: Anti-proliferative and apoptotic activities of extracts from 121 recipes selected from 56,137 recipes in the Thai medicinal plant recipe "MANOSROI II" database were investigated in two cancer cell lines including human mouth epidermal carcinoma (KB) and human colon adenocarcinoma (HT-29) cell lines using sulforhodamine B (SRB) assay and acridine orange (AO) and ethidium bromide (EB) staining technique, respectively. Results and conclusions: In the SRB assay, recipes NE028 and, S003 gave the highest anti-proliferation activity on KB and HT29 with the IC 50 values of 2.48 ± 0.24 and 6.92 ± 0.49 μg/ml, respectively. In the AO/EB staining assay, recipes S016 and NE028 exhibited the highest apoptotic induction in KB and HT-29 cell lines, respectively. This study has demonstrated that the three Thai medicinal plant recipes selected from "MANOSROI II" database (NE028, S003 and S016) gave active anti-cancer activities according to the NCI classification which can be further developed for anti-cancer treatment. © 2012 Elsevier Ireland Ltd. All rights reserved.